Assessment of Waste Animal Fats (WAFS) Biodiesel Production Potential as an Alternative Fuel for Zambia: A Case Study of Southern Province - Silungwe, Peter (Engineering And Technology Journal, 2024)
The volatility in global fuel prices and the desire to reduce energy dependency on fossil fuels has necessitated the speeding up of alternative energy supply sources. Coupled to this is the global urgent need to reduce the accumulation of CO2 and green house gas (GHG) emissions as a result of fossil fuels production and use. Further, the mandate by united nations to move towards sustainably produced energy for the transportation, and power generation demands that we seek energy solutions that meet reduced negative impact on the environment. It is in this regard that this study seeks alternatives in waste animal fats (WAFs) biodiesel as an option that could meet the ever increasing demand for fossil fuel in the transport sector and power generation. For the transport sector and power generation , the biodiesel maybe blended with the fossil diesel in the approved ratios as stipulated by the Energy Regulation Board and the Zambia Bureau of Standards to help mitigate the net GHG and CO2 emissions. The biodiesel production in this study was based on the modified two-step process. These two steps involved passing the feedstock through esterification using sulphuric acid as catalyst and there after base catalysed using sodium hydroxide in a process referred to as transesterification. The resulting products in the esterification process are the esters and water whilst in the transesterification are the biodiesel and glycerol. The feedstock used are those of waste animal fats (WAFs) of cattle, pig and chicken that has been discarded from meat processing and animal slaughter houses. The feedstocks have been carefully selected based on the animals raised in the country with a bigger slaughtered population as well as reared. The population of animals reared and slaughtered annually are obtained from the Zambia Ministry of Agriculture animal population census records. Based on these records, the preferred feedstock sources where obtained. The study further 1. explored the economic potential of the biodiesel production for the Zambian government and beyond. 2. compared some of the characteristics of WAF biodiesel to that of imported fossil diesel 3. affirmed that WAF biodiesel has a very good impact in reducing environmental pollution as WAF dumping to land fills and the cost of disposal is reduced. Also,WAF biodiesel is bio-degradable. Thus, moving closer to an effective sustainable development as required by the united nations sustainability goals if full scale production is implemented in Zambia.